Utilization of Natural Zeolites and Fly Ash (Coal) Mixture Physically Activated Using Furnace As A Pellet - shaped Air Filter To Increase Engine Torque, Tecumseh TD110. 4-Stroke Petrol Motor - yudi risano (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2022)
An air filter made from a mixture of natural zeolite and coal fly ash can be used to remove nitrogen (N2) and moisture (H2O) in the air. This filter can produce oxygen-rich air (O2) flowing into the combustion chamber to increase the quality of the combustion process so that complete combustion occurs and improve engine torque. In this research the filter was made from a physically activated mixture of natural zeolite and fly ash through heating in a furnace for 1 hour with temperature variations (200oC, 250oC, 300oC, 350oC), mass variations (50%, 75%, 100%) and variations in the composition of Z100%:F0%, Z75%:F25%, Z50%:F50%, Z25%:F75%, Z0%:F100%. Tests were carried out using a 4-stroke gasoline engine of Tecumseh TD110 located in the Motor Bakar and Propulsion Laboratory of the Mechanical Engineering Department, University of Lampung. Test results show that the biggest improvement in torque occurs in using a filter composition of Z50%:F50%, namely by 28.41%. The followed filter of the composition of Z75%:F25% is as big as 28.31%. The activation temperature of 350oC can improve the torque by 35.08%.